MEDICAL EDUCATION IN THE UZBEKISTAN. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The people of Uzbekistan are well educated and take education as the essential thing to have in life. Even the students from foreign countries come here to pursue their medical education. This country offers a unique environment for education. Studying Medical Doctor Degree in Uzbekistan is an ideal option for Medical Aspirants.